AR Makeup Tester: Design and Development of Augmented Reality based on Makeup Tester to support Product Testing - Chandran, Tineswaran; Othman, Fakri (Applied Information Technology And Computer Science, 2022)
Augmented reality is a real-world environment where objects in it are enhanced and generated by computer. The implementation of Augmented Reality in cosmetic industry gives user more enriched experience especially in virtual makeup tester. In this pandemic era, all makeup boutiques and stores are no longer using physical makeup testers. This is a way to prevent the spread of coronavirus. So, customers had to buy makeup kits without testing them. The proposed solution is to develop a virtual makeup tester using Augmented Reality that allow customers to test their makeup product virtually in real time before purchasing them online. Therefore, Multimedia Mobile Content Development methodology is used to develop AR Makeup Tester that works as a virtual cosmetic tester. With Unity Engine and Microsoft Visual Studio AR Makeup Tester is developed and went through testing phase. The testing results using System Usability Scale shows the user acceptance level of AR Makeup Tester is 92%, which falls in acceptable range.